2021
DOI: 10.3390/su132413528
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Diffusion: A Systematic Literature Review of Innovation Scaling

Abstract: Innovation is essential for our ability to overcome global issues such as climate change, natural resource depletion, and inequality. A central aspect of innovation is the scaling process. While an abundance of studies on innovation scaling exist in many different disciplines, there is a lack of shared understanding of what scaling means and how it can be successfully achieved. This systematic literature review addresses both these issues by reviewing 147 articles on “innovation scaling” making several contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…Domain expertise in the field of eating disorders, healthcare management, sensor technologies, internet of things (IoT), big data, data science, artificial intelligence is required, among others. However, global challenges such as the COVID-19 pandemic or climate change, have demonstrated that the deployment of intelligent systems is feasible through cooperation and consilience across different disciplines, and it fosters innovation scaling [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Domain expertise in the field of eating disorders, healthcare management, sensor technologies, internet of things (IoT), big data, data science, artificial intelligence is required, among others. However, global challenges such as the COVID-19 pandemic or climate change, have demonstrated that the deployment of intelligent systems is feasible through cooperation and consilience across different disciplines, and it fosters innovation scaling [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…problemas como los del sector de agua y saneamiento en ALC de manera efectiva (Breaugh et al, 2021). Al escalar innovaciones en AyS se optimizan los recursos, se producen ganancias económicas y de conocimiento para el sector y se genera nuevo valor.…”
Section: El Concepto De Escalamiento De La Innovación En El Sector De...unclassified
“…Regarding application, challenges are associated with the general dissemination and technological scaling of innovation [74]. Future research could address the concept in its practical application, evaluating the success of innovations in terms of the design of goods oriented towards efficiency and considering technological maturity and the cost of acquiring technology.…”
Section: Application In Product and Service Design And Developmentmentioning
confidence: 99%